Developing an Integrated, Brief Biobehavioral HIV Prevention Intervention for High-Risk Drug Users in Treatment: The Process and Outcome of Formative Research - Shrestha, Roman; Altice, Frederick; Karki, Pramila; Copenhaver, Michael (Frontiers in Immunology, 2017)
To date, HIV prevention efforts have largely relied on singular strategies (e.g., behavioral or biomedical approaches alone) with modest HIV risk reduction outcomes for people who use drugs (PWUD), many of whom experience a wide range of neurocognitive impairments (NCI). We report on the process and outcome of our formative research aimed at developing an integrated bio-behavioral approach that incorporates innovative strategies to address the HIV prevention and cognitive needs of high risk PWUD in drug treatment. Our formative work involved first adapting an evidence-based behavioral intervention - guided by the ADAPT-ITT model - and then combining the behavioral intervention with an evidence-based biomedical intervention for implementation among the target population. This process involved eliciting data through structured focus groups with key stakeholders – members of the target population (n=20) and treatment providers (n=10). Analysis of focus group data followed a thematic analysis approach utilizing several qualitative data analysis techniques, including inductive analysis and cross-case analysis. Based on all information, we integrated the adapted Community-friendly Health Recovery Program (CHRP) – a brief evidence-based HIV prevention behavioral intervention – with the evidence-based biomedical component (i.e., pre-exposure prophylaxis: PrEP), an approach that incorporates innovative strategies to accommodate individuals with NCI. This combination approach – now called the Bio-Behavioral Community-friendly Health Recovery Program (CHRP-BB) – is designed to address HIV-related risk behaviors and PrEP uptake and adherence as experienced by many PWUD in treatment. This study provides a complete example of the process of selecting, adapting, and integrating the EBIs – taking into account both empirical evidence and input from target population members and target organization stakeholders. The resultant brief evidence-based bio-behavioral approach could significantly advance primary prevention science by cost-effectively optimizing PrEP adherence and HIV risk reduction within common drug treatment settings.